Transição do cuidado na saúde: a construção de um conceito pelo/para Serviço Social - Morés, Fernanda Brenner (2021)
This dissertation investigates how the work of social workers in Health Care Transition has been constituted, and seeks through its objectives to analyze the concept of Care Transition in Brazilian health policy and its relationship with the principle of integrality, to identify the challenges and potentialities of the Transition of Care in the Health Care Network (RAS), in order to contribute to the qualification of the professional practice of the Social Worker and consolidation of the principle of integrality in the SUS, considering the consequences of the deterioration of the neoliberal ideology in politics of health. It highlights the implications that went through the elaboration of this study caused by the coronavirus pandemic. For this, a qualitative study was conducted, guided by the theoretical framework of the critical dialectical method, which makes it possible to contribute to the explanation of the object of study in relation to the social reality and to guide the interventional processes. The research scenario is a Health Services Complex, which integrates services from all parts of the RAS, and the research participants are social assistants linked to hospitalization units, family health units and home care program. Data collection was developed in the form of data triangulation to surround the object and answer the objectives of this study. In order to research the work of the social worker in the Transition of Care, the collective research collection technique Metaplan was used through online meetings, due to the implications of the coronavirus pandemic that crossed this study. To qualify the process of investigation and unveiling of the object, we used the type of documentary research on the legal documents of health policy and survey and analysis of the electronic medical records of the users of the hospitalization. From the literature review and the analysis of health legislation, it was identified that, despite the incipience of production on the theme and the fragility in the definition of a concept, the Transition of Care is associated with the expanded concept of health and in line with the principles of the Unified Health System (SUS) in relation to guaranteeing access, integrality of actions, user autonomy and right to information. The analysis of the testimonies of the social assistants in the construction of the Transition of Care concept evidenced the collective character of the Transition of Care confirmed through the meeting between the different actors in different dimensions and that as a collective strategy it fosters changes in the production of health care that can transform the reality of health policy as a whole.